Natural resource management in the hillsides of Honduras: bioeconomic modeling at the micro-watershed level - Barbier, Bruno; Bergeron, Gilles (International Food Policy Research Institute, 2001)
Barbier and Bergeron explore several hypotheses about the dynamics of natural resource management in the hillsides of La Lima and further explore the causes and consequences of the transition to vegetable production. To fully integrate agroecological factors, such as forest,